AliC and AliD of nonencapsulated Streptococcus pneumoniae enhance virulence in a Galleria mellonella model of infection by contributing to reactive oxygen species resistance - Courtney D. Thompson; Md Fahim Khan; Lucas R. G. Crosby; Shelby G. Holcomb; Ana G. Jop Vidal; Jorge E. Vidal; Jorge E. Vidal; Larry S. McDaniel; Larry S. McDaniel; Lance E. Keller; Lance E. Keller (Frontiers in Cellular and Infection Microbiology)
IntroductionNonencapsulated Streptococcus pneumoniae (NESp) are isolated worldwide. Due to the lack of capsule in NESp strains the current vaccines, that target the pneumococcal capsule are ineffective. Some NESp contain the oligopeptide transporters AliC and AliD which are required for virulence through unknown mechanisms. AliC and AliD have been previously shown to reduce rates of phagocytosis and alter the transcriptome and proteome of MNZ41. We hypothesize that oligopeptide regulated genes are responsible for reduced phagocytosis and increased survival through resistance to reactive oxygen species (ROS).MethodsTo test this a mutant library of AliC and AliD regulated genes was used in in vitro and in vivo models. ROS resistance was tested through quantifying bacterial counts after exposure to hydrogen peroxide (H2O2). A modified surface killing assay was also used to calculate resistance to phagocytosis of our mutant library. A Galleria mellonella larvae model of infection was used to determine survival curve analyses.ResultsTwo mutant genes in our library, ∆lytFN1 (CDT04) and ∆mgtC (CDT05), displayed greater sensitivity to H2O2 killing and phagocytosis compared to wildtype MNZ41. Deletion of AliD in an AliD-expressing encapsulated strain reduced virulence.ConclusionThis research demonstrates that proteins encoded by genes regulated by AliC and AliD alter susceptibility to host-derived mechanisms for bacterial clearance and increases bacterial survival in response to ROS.